2020
DOI: 10.33824/pjpr.2020.35.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and Academic Burnout: The Mediating Role of Worry and Depressive Rumination in University Students

Abstract: The present study investigated effects of perfectionism, depressive rumination (DR), and worry on academic burnout in university students. In addition mediating roles of depressive rumination and worry was explored. A sample of 515 students (237 females, 278 males) with age range of 17-27 years; (M = 20, SD = 1.66) were included from various government and private universities of Lahore. The research instruments used were: Almost Perfect Scale-Revised (APS-R; Slaney, Rice, Mobley, Trippi, & Ashby, 2001), R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
2
0
0
Order By: Relevance
“…Findings from the current study are in agreement with previous results showing an association between levels of worrying and job burnout among healthcare residents [80]. A link between worry and burnout was also found among highly demanding professions, such as athletes [81] and university students [82]. Worry involves concerns about upcoming events and distress that is yet to come.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…Findings from the current study are in agreement with previous results showing an association between levels of worrying and job burnout among healthcare residents [80]. A link between worry and burnout was also found among highly demanding professions, such as athletes [81] and university students [82]. Worry involves concerns about upcoming events and distress that is yet to come.…”
Section: Plos Onesupporting
confidence: 92%
“…Chaukos et al [80] showed higher levels of worry among healthcare residents that have also reported high levels of burnout. This is in line with studies showing a similar relation between worry and burnout among highly demanding professions, such as athletes [81] and university students [82]. Consistently, prior studies have also suggested a strong relationship between trait anxiety and burnout [83][84][85].…”
Section: Introductionsupporting
confidence: 90%